Partial Mandibulectomy Rehabilitation of Keratocystic Odontogenic Tumour Case in Neutral Zone - Halim, Mohamad Syahrizal; Ariff, Tengku Fazrina Tengku Mohd (Hindawi Publishing Corporation, 2018)
Restoring the patient’s missing dentition secondary to partial mandibulectomy of KCOT is important to improve function and aesthetics. The patient presented with a significant loss of alveolar bone which makes the fabrication of rehabilitation prosthesis a significant challenge. A neutral-zone impression technique is helpful in determining the exact space to be restored without compromising aesthetics and it avoids functional muscle displacement that may displace the prosthesis. This article describes the neutral zone impression technique to record a patient's functional muscular movement in guiding the setting of acrylic teeth and denture flange in the neutral zone area. This technique is very useful for postsurgical cases with significant loss of alveolar bone.